Water-soluble star-shaped brush-like block copolymers: synthesis and application as multicompartment nanoreactors for fabrication of quantum dot colloidal nanocrystal clusters. Issue 117 (11th November 2015) - Bai, Junjing; Wang, Xiaobing; Fu, Peng; Cui, Zhe; Zhao, Qingxiang; Pang, Xinchang; Liu, Minying
Abstract : Water-soluble multi-arm star-shaped brush-like block copolymers of (PEO- g -PAA)- b -PEO were synthesized and exploited as polymeric nanoreactors to structure-direct in situ fabrication of CdSe QD colloidal nanocrystal clusters. Abstract : A series of novel water-soluble multi-arm star-shaped brush-like block copolymers, composed of poly(ethylene oxide) (PEO) as the main chain, poly(acrylic acid) (PAA) as functional graft chains, and a second PEO block as the shell ( i.e., multi-arm star-shaped brush-like block copolymer (PEO- g -PAA)- b -PEO) with different molecular weights and grafting density, were rationally designed and synthesized by a combination of anionic copolymerization and atom transfer radical polymerization (ATRP). The anionic ring-opening copolymerization of ethylene oxide (EO) and ethoxyethyl glycidyl ether (EEGE) was conducted first by using α-cyclodextrin (α-CD) with 18 hydroxyl groups and diphenylmethyl sodium (DPMNa) as co-initiator system. The monomer reactivity ratios for EO and EEGE were also determined: r 1(EO) = 1.18 ± 0.03 and r 2(EEGE) = 0.79 ± 0.01, respectively. Then the resulting multi-arm star-shaped copolymers of poly(EO- co -EEGE) with hydroxyls as end functional groups were utilized as star-shaped macroinitiators to sequentially initiate the anionic ring-opening polymerization of monomer EO for the second block hydrophilic homopolymer PEO chain grown on the first block poly(EO- co -EEGE) arm end, and then the ethoxyethyl groups of the star-shaped block copolymers of poly(EO- co -EEGE)- b -PEO obtained were removed by hydrolysis. The formed multi-arm star-shaped block copolymers of EO and glycidol (Gly) with multi-pendant hydroxymethyls (star-shaped block copolymer poly(EO- co -Gly)- b -PEO) were then esterified by the reaction of the pendant hydroxyl groups of glycidol units of copolymers with 2-bromoisobutyryl bromide, and the resulting star-shaped brush-like macroinitiators were used to initiate the grafting polymerization of t -butyl acrylate ( t BA) by ATRP technique. Finally, the tert -butyl ester groups of P t BA grafting side chains were selectively hydrolyzed in trifluoroacetic acid ​(TFA) to obtain the water-soluble multi-arm star-shaped brush-like block copolymer (PEO- g -PAA)- b -PEO. The water-soluble star-shaped brush-like (PEO- g -PAA)- b -PEO, which consisted of a functional PAA domain as the core and a hydrophilic PEO domain as the shell, were exploited as polymeric nanoreactors to structure-direct in situ fabrication of CdSe quantum dots (QDs) colloidal nanocrystal clusters composed of primary CdSe nanocrystals as subunits, with the secondary structures of CdSe nanocrystals. Spherical CdSe colloidal nanocrystal clusters were intimately and permanently capped with hydrophilic PEO chains on the surface to render the resulting clusters with high water dispersible property.